Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 46245 by rpseelam last updated on 23/Oct/18

(1/(1.3.5))+(1/(3.5.7))+(1/(5.7.9))+.....nth term

11.3.5+13.5.7+15.7.9+.....nthterm

Commented by maxmathsup by imad last updated on 23/Oct/18

let S_n =Σ_(k=0) ^n   (1/((2k+1)(2k+3)(2k+5)))   let find  S_n    let decompose  F(x)=(1/((2x+1)(2x+3)(2x+5))) ⇒F(x)=(a/(2x+1)) +(b/(2x+3)) +(c/(2x+5))  a =lim_(x→−(1/2))   (2x+1)F(x)= (1/(2.4)) =(1/8)  b=lim_(x→−(3/2))    (2x+3)F(x)= (1/((−2).2)) =−(1/4)  c=lim_(x→−(5/2))   (2x+5)F(x)= (1/((−4).(−2))) =(1/8) ⇒  F(x)= (1/(8(2x+1))) −(1/(4(2x+3))) +(1/(8(2x+5))) ⇒  S_n =(1/8)Σ_(k=0) ^n   (1/(2k+1)) −(1/4) Σ_(k=0) ^n   (1/(2k+3)) +(1/8) Σ_(k=0) ^n  (1/(2k+5)) but  Σ_(k=0) ^n  (1/(2k+3)) =_(k=j−1)    Σ_(j=1) ^(n+1)   (1/(2j+1)) =Σ_(j=0) ^n  (1/(2j+1)) −1 +(1/(2n+1))  Σ_(k=0) ^n   (1/(2k+5)) =_(k=j−2)  Σ_(j=2) ^(n+2)   (1/(2j +1)) =Σ_(j=0) ^n  (1/(2j+1)) −1−(1/3) +(1/(2n+1)) +(1/(2n+5))  S_n =(1/8) Σ_(k=0) ^n  (1/(2k+1)) −(1/4) Σ_(j=0) ^n  (1/(2j+1)) +(1/4) −(1/(4(2n+1)))  +(1/8)Σ_(j=0) ^n  (1/(2j+1)) +(1/8)(−(4/3)) +(1/(8(2n+1))) +(1/(8(2n+5)))  =(1/4) −(1/6)  −(1/(4(2n+1))) +(1/(8(2n+))) +(1/(8(2n+5)))  =(1/(12)) −(1/(8(2n+1))) +(1/(8(2n+5))) =(1/(12)) +(1/8){(1/(2n+5)) −(1/(2n+1))}  =(1/(12)) +(1/8){((−4)/((2n+1)(2n+5)))} =(1/(12)) −(1/(2(2n+1)(2n+5))) .

letSn=k=0n1(2k+1)(2k+3)(2k+5)letfindSnletdecomposeF(x)=1(2x+1)(2x+3)(2x+5)F(x)=a2x+1+b2x+3+c2x+5a=limx12(2x+1)F(x)=12.4=18b=limx32(2x+3)F(x)=1(2).2=14c=limx52(2x+5)F(x)=1(4).(2)=18F(x)=18(2x+1)14(2x+3)+18(2x+5)Sn=18k=0n12k+114k=0n12k+3+18k=0n12k+5butk=0n12k+3=k=j1j=1n+112j+1=j=0n12j+11+12n+1k=0n12k+5=k=j2j=2n+212j+1=j=0n12j+1113+12n+1+12n+5Sn=18k=0n12k+114j=0n12j+1+1414(2n+1)+18j=0n12j+1+18(43)+18(2n+1)+18(2n+5)=141614(2n+1)+18(2n+)+18(2n+5)=11218(2n+1)+18(2n+5)=112+18{12n+512n+1}=112+18{4(2n+1)(2n+5)}=11212(2n+1)(2n+5).

Answered by tanmay.chaudhury50@gmail.com last updated on 23/Oct/18

T_n =(1/({1+(n−1)2}{3+(n−1)2}{5+(n−1)2}))  T_n =(1/((2n−1)(2n+1)(2n+3)))  S_n =C−(1/((2n+1)(2n+3)×2×2))  put n=1   S_1 =T_1 =(1/(15))  (1/(15))=C−(1/(4(3)(5)))  C=(1/(15))+(1/(60))=((4+1)/(60))=(1/(12))  S_n =(1/(12))−(1/(4(2n+1)(2n+3)))  checking the answer  by follosing proof  1)S_1 =T_1   2)S_2 =T_1 +T_2   3)S_3 =T_1 +T_2 +T_3   T_n =(1/((2n−1)(2n+1)((2n+3)))  T_1 =(1/(1×3×5))=(1/(15))        S_1 =(1/(12))−(1/(4×3×5))=(1/(15))  T_1 =S_1  proved  T_2 =(1/(3×5×7))=(1/(105))  T_3 =(1/(5×7×9))=(1/(315))  T_1 +T_2 =(1/(15))+(1/(105))=(8/(105))  S_n =(1/(12))−(1/(4(2n+1)(2n+3)))  S_2 =(1/(12))−(1/(4×5×7))=(8/(105))  so S_2 =T_1 +T_2   proved  T_1 +T_2 +T_3 =(8/(105))+(1/(315))=(5/(63))  S_3 =(1/(12))−(1/(4×7×9))=(5/(63))  so my answer iscorrect...

Tn=1{1+(n1)2}{3+(n1)2}{5+(n1)2}Tn=1(2n1)(2n+1)(2n+3)Sn=C1(2n+1)(2n+3)×2×2putn=1S1=T1=115115=C14(3)(5)C=115+160=4+160=112Sn=11214(2n+1)(2n+3)checkingtheanswerbyfollosingproof1)S1=T12)S2=T1+T23)S3=T1+T2+T3Tn=1(2n1)(2n+1)((2n+3)T1=11×3×5=115S1=11214×3×5=115T1=S1provedT2=13×5×7=1105T3=15×7×9=1315T1+T2=115+1105=8105Sn=11214(2n+1)(2n+3)S2=11214×5×7=8105soS2=T1+T2provedT1+T2+T3=8105+1315=563S3=11214×7×9=563somyansweriscorrect...

Commented by tanmay.chaudhury50@gmail.com last updated on 23/Oct/18

my ans is correct...

myansiscorrect...

Commented by rpseelam last updated on 24/Oct/18

that is excellent sir. thanks

thatisexcellentsir.thanks

Commented by tanmay.chaudhury50@gmail.com last updated on 24/Oct/18

most welcome...

mostwelcome...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com